PENTINGNYA PERAN ORANG TUA DALAM MENCEGAH STUNTING DEMI MASA DEPAN ANAK - Ernawati, Sri; Pratiwi, Aliah; Ramadhoani, Mulyati; Sofiyanti, Nur Awalia; Jumratu, Jumratu; Mutiara, Mutiara; Afwan Riyadin, Muhammad (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
Stunting is a description of chronic malnutrition status during growth and development from early life. The main causes of stunting include inadequate nutrition and nutritional intake for children, incorrect parenting patterns due to lack of knowledge and education for pregnant and breastfeeding mothers, poor environmental sanitation. Some village residents have minimal knowledge about stunting, so KKN-T MBKM STIE BIMA students collaborate with the village government with PKK women to carry out socialization and outreach activities on stunting prevention. This activity contains advice on preventing and handling stunting appropriately. Then the bad impacts that occur if you don’t adopt a healthy and clean lifestyle can cause stunting in children and pregnant women. From this activity, the results and targets that KKN students want to achieve are citizens who have high enthusiasm so that this outreach activity runs smoothly. Village residents no longer feel strange and know about how to prevent stunting.